Autistic traits in women with primary dysmenorrhea: a case–control study - Toy H (Dove Medical Press, 2016)
Harun Toy,1 Arzu Hergüner,2 Sevcan Şimşek,1 Sabri Hergüner3 1Department of Obstetrics and Gynecology, Meram Faculty of Medicine, Necmettin Erbakan University, 2Child and Adolescent Psychiatry Clinic, Konya Training and Research Hospital, 3Department of Child and Adolescent Psychiatry, Meram Faculty of Medicine, Necmettin Erbakan University, Konya, Turkey Objectives: Recent studies have shown that women with autism spectrum disorder have higher rates of menstrual problems, including irregular menstrual cycles, unusually painful periods (dysmenorrhea), and excessive menstrual bleeding. In this study, we investigated the autistic traits in female university students with primary dysmenorrhea (PD). Methods: Seventy females with PD and 70 females without PD were enrolled in the study. The Autism Spectrum Quotient (AQ) was used to measure autistic traits and the Brief Symptom Inventory was used for evaluating anxiety and depression levels. The dysmenorrheal pain was assessed by visual analog scale (VAS), coded from 0 to 10. Weight and height were measured, and the body mass index was calculated. Results: There were no statistical differences between the groups in terms of age, duration of education, and body mass index. Women with PD had higher AQ – Total, and AQ – Attention Switching subscale scores than subjects without PD. Spearman analysis revealed that AQ – Total and AQ – Attention Switching scores were correlated with VAS. According to the linear regression analysis, VAS was predicted only by AQ – Attention Switching subscale. Conclusion: Our findings showed an association between autistic traits and dysmenorrhea in typically developing females. Keywords: primary dysmenorrhea, autistic traits, androgens